HUBUNGAN DUKUNGANAORANG TUA TERHADAP MOTIVASI BELAJAR DALAMAPEMBELAJARAN JARAK JAUH PADA PESERTA DIDIK KELAS VADI SEKOLAH DASAR NEGERI KAMAL 06 - Fitrah Tristiana Sumarah; Wati Sukmawati (Universitas PGRI Yogyakarta, 2021)
This study aims to determineathe relationshipabetween parentalasupportaand learning motivationain distance learning. This research was conducted at SD Negeri Kamal 06. The hypothesisaof this researchais that thereais a positive relationship between parental support and learning motivation in distance learning in class V students at SD Negeri Kamal 06. The research subjects are students of SD Negeri Kamal 06 class V totaling 67 students. The sampling technique used was total sampling. Theameasuring instrument used is aaparental support scale and a learning motivation scale. The data analysis technique uses product moment correlation analysis.The results showed that there was a significant positive relationship between parental support and learning motivation in distance learning in fifth grade students at SD Negeri Kamal 06 with a value of r = 0.543 ; p = 0.000 (p <0.05). Theaconclusion in this studyais that there is aasignificant positive relationship betweenaparental support and learning motivation in distance learning in fifth grade students at SD Negeri Kamal 06. The effective contribution of the parental support variable to student learning motivation is 29.5% as indicated by the coefficient of determination. (r2) of 0,295, this means that there are 70.5% of other factors that affect student learning motivation.